Comparative evaluation of surface topography of tooth prepared using erbium, chromium: Yttrium, scandium, gallium, garnet laser and bur and its clinical implications - Mahesh Verma; Pooja Kumari; Rekha Gupta; Shubhra Gill; Ankur Gupta (Wolters Kluwer Medknow Publications, 2015)
Background: Erbium, chromium: Yttrium, scandium, gallium, garnet (Er, Cr: YSGG) laser has been successfully used in the ablation of dental hard and soft tissues. It has been reported that this system is also useful for preparing tooth surfaces and etching, but no consensus exist in the literature regarding the advantage of lasers over conventional tooth preparation technique. Materials and Methods: Labial surfaces of 25 extracted human maxillary central incisors were divided into two halves. Right half was prepared with diamond bur and left half with Er, Cr; YSGG laser and a reduction of 0.3-0.5 mm was carried out. Topography of prepared surfaces of five teeth were examined under scanning electron microscope (SEM). The remaining samples were divided into 4 groups of 10 specimens each based on the surface treatment received: One group was acid etched and other was nonetched. Composite resin cylinders were bonded on prepared surfaces and shear bond strength was assessed using a universal testing machine. Results: The SEM observation revealed that the laser prepared surfaces were clean, highly irregular and devoid of a smear layer. Bur prepared surfaces were relatively smooth but covered with smear layer. Highest bond strength was shown by laser prepared acid etched group, followed by bur prepared the acid etched group. The bur prepared nonacid etched group showed least bond strength. Conclusions: Er, Cr: YSGG laser can be used for preparing tooth and bond strength value achieved by laser preparation alone without surface treatment procedure lies in the range of clinical acceptability.